2015
DOI: 10.1016/j.jneuroling.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Neural changes underlying successful second language word learning: An fMRI study

Abstract: a b s t r a c tA great deal of research has examined behavioral performance changes associated with second language learning. But what changes are taking place in the brain as learning progresses? How can we identify differences in brain changes that reflect successes of learning? To answer these questions, we conducted a functional magnetic resonance imaging (fMRI) study to examine the neural activities associated with second language word learning. Participants were 39 native English speakers who had no prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 66 publications
(91 reference statements)
8
100
0
1
Order By: Relevance
“…Moreover, already in the early 1900s, the left lower parietal region was delineated as the "language talent area" by the German neurologist Pötzl (1925), who pointed it out to be the site underlying the exceptionality of the brains of multilinguals (Della Rosa et al, 2013). His findings seem to converge with recent neuroimaging investigations: the inferior parietal cortex has been shown to play a crucial role in complex language functions and memory processes, phonological representation, semantic integration, and second language vocabulary learning (Della Rosa et al, 2013;Li, Legault, & Litcofsky, 2014;Mechelli et al, 2004;Yang, Gates, Molenaar, & Li, 2015). More specifically, O'Connor, Han, & Dobbins (2010) have found the angular and supramarginal gyri to act as markers of violations in memory expectations, where a violation is a sign of contradiction between retrieval outcomes and expectations, and argued for the importance of both superior and inferior aspects of the lateral parietal regions for noting a lack of correspondence between what is anticipated from memory retrieval, and what is unusual.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, already in the early 1900s, the left lower parietal region was delineated as the "language talent area" by the German neurologist Pötzl (1925), who pointed it out to be the site underlying the exceptionality of the brains of multilinguals (Della Rosa et al, 2013). His findings seem to converge with recent neuroimaging investigations: the inferior parietal cortex has been shown to play a crucial role in complex language functions and memory processes, phonological representation, semantic integration, and second language vocabulary learning (Della Rosa et al, 2013;Li, Legault, & Litcofsky, 2014;Mechelli et al, 2004;Yang, Gates, Molenaar, & Li, 2015). More specifically, O'Connor, Han, & Dobbins (2010) have found the angular and supramarginal gyri to act as markers of violations in memory expectations, where a violation is a sign of contradiction between retrieval outcomes and expectations, and argued for the importance of both superior and inferior aspects of the lateral parietal regions for noting a lack of correspondence between what is anticipated from memory retrieval, and what is unusual.…”
Section: Discussionsupporting
confidence: 75%
“…For example, the WM microstructure of the left arcuate fasciculus, which connects the left IFG with left IPL and STG, has been associated with novel word learning (Ló pez-Barroso et al, 2013). Yang et al (2015) showed that successful compared with less successful learners of novel words had stronger connectivity within the left IFG-IPL-STG circuit during a word-picture association task. Gray matter density of the left IFG was corrected positively with L2 lexical efficiency, measured by the number of words produced in a timed verbal fluency task, whereas gray matter density of the supramarginal gyrus reflected the number of words known (Grogan et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…The inferior parietal region, along with the temporal lobe, is consistently active in semantic processing tasks (Binder & Desai, 2011; Price, 2010) and the inferior parietal regions in particular become better integrated into a larger word-learning network for learners who are able to successfully associate phonological strings with meaning (Yang, Gates, Molenaar, & Li, 2015). However, our task did not provide learners with any semantic information for the words contained in the input.…”
Section: Discussionmentioning
confidence: 99%